2021
DOI: 10.1097/ijg.0000000000001837
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of 10-2 Visual Field Loss Using Optical Coherence Tomography and 24-2 Visual Field Data

Abstract: Precis: Using standard glaucoma structural and functional tests, clinicians accurately predicted the presence/absence of 10-2 glaucomatous visual field (VF) loss in 90% of the eyes in this study.Purpose: To investigate how well clinicians with variable experience can predict the presence and location of 10-2 VF loss using structural and functional data that are routinely obtained for glaucoma assessment.Methods: Within a test set of 416 eyes (210 subjects) who were diagnosed glaucoma suspect or primary open-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Although the results from this study show that presence/absence of baseline 10-2 VF loss provides insight regarding the future course of glaucomatous disease, a recent report indicated that accurate prediction of presence/absence of 10-2 VF loss can be achieved in a majority of cases using a combination of standard structural (OCT) and functional (24-2) measures. 33 Accordingly, that study suggests that actually completing the 10-2 VF test may be unnecessary for risk assessment purposes. However, although that study demonstrated ~90% accuracy for predicting presence/absence of 10-2 VF loss, the predictive capability was imperfect with residual false-positive and false-negative errors.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although the results from this study show that presence/absence of baseline 10-2 VF loss provides insight regarding the future course of glaucomatous disease, a recent report indicated that accurate prediction of presence/absence of 10-2 VF loss can be achieved in a majority of cases using a combination of standard structural (OCT) and functional (24-2) measures. 33 Accordingly, that study suggests that actually completing the 10-2 VF test may be unnecessary for risk assessment purposes. However, although that study demonstrated ~90% accuracy for predicting presence/absence of 10-2 VF loss, the predictive capability was imperfect with residual false-positive and false-negative errors.…”
Section: Discussionmentioning
confidence: 96%
“…40,41 Yet, because adding the 10-2 VF test to the baseline testing protocol would be expected to increase burdens to patients, providers, payers, and practice patterns, the benefits of adopting the test for routine use need to be substantial and well supported by published evidence. Although current evidence demonstrating how the 10-2 test improves clinical management and outcomes in early and moderate glaucoma continues to accumulate, 11,12,[33][34][35][36][37][39][40][41] it can be argued that the evidence already supports 10-2 VF testing for monitoring progression, particularly in eyes with history of disc hemorrhage. In addition, the results from this study suggest that 10-2 testing provides independent and valuable information for predicting future glaucoma progression that is more precise than using central 24-2 VF information alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation